Exploring Organizational Sustainability: Themes, Functional Areas, and Best Practices - Waqas Nawaz (10783445) (2019)
Most of the sustainability management models proposed in the literature are based on conceptual designs, which limits their potential to be applied in practice. In order to develop a holistic tool for organizational sustainability management, it is imperative to account for, and integrate, the sustainability best practices in the conceptual models. The primary objective of this work is to explore the organizational sustainability themes, functional areas, and the corresponding best practices of the most sustainable organizations. Based on the results, we aim to propose a framework which can support the theoretical models. The starting set of 100 most sustainable organizations is obtained through a well-defined sustainability ranking, Global 100. A systematic method is developed and applied to screen the organizational reports between 2012 and 2016. As a result, 61 reports of 20 organizations are selected for review. We used grounded mechanism to conduct the review. The results of the review indicate that the most sustainable organizations rely on the following nine themes to advance their sustainability performance: (i) resource optimization and minimization of waste and emissions; (ii) business and operational excellence; (iii) corporate citizenship and social development; (iv) research and innovation; (v) procurement, supply chain, and logistics; (vi) governance; (vii) sustainability management tools; (viii) employee relations; and (ix) health, wellness, safety, and security. In addition, there are around 38 functional areas which are of great significance to sustainability managers from an applied perspective and to researchers for constructing sustainability management models. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su11164307